Biaxial Loading Capacity of H-Type Reinforced Concrete Electric Poles - Abolfazl Eslami; Moein Ramezanpour; Ehsan Hematpoury Farokhy; Mohammad Dehghani Sanij (Journal of Rehabilitation in Civil Engineering)
H-type reinforced concrete poles are nowadays widely used as an economical and cost-effective substitute for wooden poles in power transmission lines. Although these poles are frequently subjected to biaxial loading in real field application, their biaxial interaction curves yet await detailed investigation. The current study was aimed at developing the biaxial bending interaction curves for H-type utility poles considering the measurements stipulated by the relevant standards and codes. Towards this, two commonly used H-type electric poles (i.e., 9 and 12 m ones with a normal strength of 400 kgF) were constructed, cured, and loaded at angles of 0, 30, 60, and 90 degrees with respect to their minor principal axes. The experimental results were described in terms of load-displacement curves, developed strains, cracking pattern, failure modes, and biaxial loading interaction curve. The obtained interaction diagrams can be reliably used to estimate the loading capacity of electric poles under biaxial loading in real field applications.